The Effect of Kerokan to Liver Function of Hepatitis B Patients - Hanum, Nur Adiba; Ismalayani, Ismalayani; Juliansyah, Rahmad Aswin; Syokumawena, Syokumawena; Pastari, Marta; Kusuma, Hanna Sari Widya; Arinta, Yukko (Global Medical & Health Communication (GMHC), 2019)
Kerokan is an alternative therapy done by rubbing and pressing the skin surface using oil and a blunt object. This treatment has a hepatoprotective effect as it increases heme oxygenase-1, an essential enzyme in heme catabolism. In hepatitis B, heme oxygenase-1 plays a vital role to fight oxidative stress. Hence the damage on liver cells can be reduced or even prevented. Damaged cells indicate by the production of aspartate aminotransferase (AST/SGOT) and alanine aminotransferase (ALT/SGPT) enzymes that accumulated in the bloodstream. This study aimed to investigate the effect of kerokan to liver function by analyzing SGOT and SGPT levels in hepatitis B patients. These were an experimental study with a pre-test post-test control group design conducted in the public health center in Palembang in October 2016. Statistical analysis used the unpaired t test and paired. The research subjects were 30 patients with inactive carrier and chronic hepatitis B. The levels of SGOT and SGPT were determined using the IFCC method. The levels of SGOT in control (19.53±3.44 U/L) and treatment group (20.46±4.53 U/L, Δ=0.93) after 24–48 hours were not statistically different (p=0.53). Also, the levels of SGPT in control (18.66±5.40 U/L) and treatment group (19.80±9.25 U/L, Δ=1.13) after 24–48 hours were also not statistically different (p=0.68) as well. In conclusion, the liver cells of inactive carrier and chronic hepatitis B patients were not damaged (necrosis) after kerokan therapy, and the levels of SGOT and SGPT were still in the normal range. EFEK KEROKAN TERHADAP FUNGSI HEPAR PASIEN HEPATITIS BKerokan merupakan terapi alternatif yang dilakukan dengan menggosok dan menekan permukaan kulit menggunakan minyak dan benda tumpul. Pengobatan ini bersifat hepatoprotektif, yaitu meningkatkan produksi enzim heme oxygenase-1 dalam katabolisme heme. Pada hepatitis B, heme oxygenase-1 berperan penting dalam menangkal radikal bebas sehingga dapat mengurangi atau mencegah kerusakan sel hepar. Kerusakan sel hepar diindikasikan oleh produksi enzim aspartate aminotransferase (AST/SGOT) dan alanine aminotransferase (ALT/SGPT) yang terakumulasi dalam pembuluh darah. Penelitian ini bertujuan mengetahui pengaruh kerokan pada fungsi hepar dengan menganalisis kadar SGOT dan SGPT pada pasien hepatitis B. Penelitian eksperimental ini menggunakan desain pre-test post-test control group yang dilakukan di puskesmas di Palembang pada Oktober 2016. Analisis statistik menggunakan uji t berpasangan dan tidak berpasangan. Subjek penelitian meliputi 30 pasien inactive carrier dan kronik hepatitis B. Kadar SGOT dan SGPT diukur dengan menggunakan metode IFCC. Kadar SGOT pada kontrol (19,53±3,44 U/L) dan grup perlakuan (20,46±4,53 U/L; Δ=0,93) setelah 24–48 jam tidak terdapat perbedaan signifikan (p=0,53). Selain itu, kadar SGPT pada kontrol (18,66±5,40 U/L) dan grup perlakuan (19,80±9,25 U/L; Δ=1,13) setelah 24–48 jam tidak menunjukkan perbedaan signifikan (p=0,68). Simpulan, sel hepar pada pasien inactive carrier dan kronik hepatitis B tidak mengalami kerusakan setelah terapi kerokan, serta kadar SGOT dan SGPT tetap dalam kondisi normal.